Do Firms Adjust Their Timely Loss Recognition in Response to Changes in the Banking Industry? - GORMLEY, TODD A.; KIM, BONG HWAN; MARTIN, XIUMIN (Journal of Accounting Research, 2012)
ABSTRACT This paper investigates the impact of changes in the banking sector on firms’ timely recognition of economic losses. In particular, we focus on the entry of foreign banks into India during the 1990s, which likely causes an exogenous increase in lender demand for timely loss recognition. Analyzing variation in both the timing and the location of the new foreign banks’ entries, we find that foreign bank entry is associated with more timely loss recognition and this increase is positively related to a firm's subsequent debt levels. The change appears driven by a shift in firms’ incentives to supply additional information to lenders and lenders seem to value this information. The increase in timely loss recognition is also concentrated among firms more dependent on external financing: private firms, smaller firms, and nongroup firms. Overall, our evidence suggests that a firm's accounting choices respond to changes in the banking industry.